ANALYSIS OF THE EFFECT MECHANISM AND CHEMICAL COMPOSITION OF COOLING LUBRICANTS IN MECHANICAL PROCESSING - Mamurov Eldor Tursunovich; Ulmasov Ahadjon Akramjon Ugli; Rakhimov Sharifjon Esonaliyevich (Web of Journals Publishing, 2024)
This study explores the efficiency of cooling lubricants used in mechanical processing, focusing on their functional mechanisms and chemical compositions. The analysis considers the influence of various factors, including the chemical properties and diversity of lubricant components, cutting conditions, and the material properties of both the workpiece and the cutting tool. The investigation also evaluates the impact of processing conditions on the overall effectiveness of cooling lubricants, providing insights into their optimization for enhanced performance and tool longevity. The findings aim to contribute to the development of more efficient and environmentally sustainable cooling lubricants in industrial applications.
Keywords: efficiency, chemical composition, operational properties, contact zone, lubricating film, washing actions, cutting parameters, lubricating actions, cooling actions, temperature, chemical reactions, processes.